The Co-occurrence of Mirror-Touch With Other Types of Synaesthesia. (November 2019) - Ward, Jamie
People with mirror-touch synaesthesia report tactile experiences on their body when seeing other people touched. Although this has been referred to as a type of synaesthesia, it is unknown whether it co-occurs with more commonly accepted variants of synaesthesia (e.g., grapheme-colour). If it did, then this would imply a common or partly shared causal mechanism. To this end, a sample of verified grapheme-colour synaesthetes ( N = 80) were given a recently developed online diagnostic measure of mirror-touch. The prevalence in this group (∼20%) was around 10 times higher than the general population. Moreover, performance on this measure was significantly related to the self-report of mirror-touch given, on average, 3 years earlier.